Incorporation of CD40 ligand or granulocyte‐macrophage colony stimulating factor into Hantaan virus (HTNV) virus‐like particles significantly enhances the long‐term immunity potency against HTNV infection. Issue 3 (March 2019) - Dong, Yuhang; Ma, Tiejun; Zhang, Xiaoxiao; Ying, Qikang; Han, Mingwei; Zhang, Muqi; Yang, Rongjin; Li, Yuan; Wang, Fang; Liu, Rongrong; Wu, Xingan
Abstract : Purpose. : Hantavirus infections cause severe haemorrhagic fever with renal syndrome (HFRS) in humans and are associated with high fatality rates. In 2017, numerous outbreaks were reported in China and Germany. This represents a significant public‐healthcare issue with no effective HFRS vaccines that offer a long‐term immune response. In this study, we investigated the long‐term humoral and cellular immune responses and protective immunity of Hantaan virus (HTNV) granulocyte‐macrophage colony stimulating factor (GM‐CSF) and CD40 ligand (CD40L) virus‐like particles (VLPs) in mice. Methodology. : GM‐CSF and CD40L VLPs were constructed via co‐transfection of pCI‐S and pCI‐M‐CD40L, and pCI‐S and pCI‐M‐GM‐CSF, into dihydrofolatereductase (dhfr)‐deficient Chinese hamster ovary cells, respectively. Mice were immunized with HTNV VLPs 2 weeks apart. The animals were challenged 6 months after immunization. Specific and neutralizing antibodies were assessed by ELISA; IFN‐γ was measured by enzyme‐linked immunospot (ELISpot) assay and effectiveness by cytotoxic T lymphocyte (CTL) cytotoxicity assays. Nucleic acid loads of HTNV were tested by quantitative real‐time PCR and viral antigen was detected via indirect ELISA. Pathological alterations were detected via haematoxylin‐eosin staining. Results. : GM‐CSF and CD40L VLPs provided stable, long‐term protection with a high titre of neutralizing antibody in mice 6 months after immunization. Furthermore, VLPs increased HTNV‐specific cellular immune responses via higher expression of IFN‐γ and CTL responses. HTNV challenge assay results showed long‐term protection against HFRS. No significant pathological alteration was observed in the organs of mice after immunization. Conclusion. : This is, to the best of our knowledge, the first report demonstrating the long‐term potency of HTNV VLP vaccines against HTNV infection and offers new insights into HTNV vaccine development.